2018
DOI: 10.7150/ijbs.24360
|View full text |Cite
|
Sign up to set email alerts
|

Overexpressed circPVT1, a potential new circular RNA biomarker, contributes to doxorubicin and cisplatin resistance of osteosarcoma cells by regulating ABCB1

Abstract: Circular RNAs (circRNAs) represent a widespread class of non-coding RNAs generated from back-splicing, with a circular loop structure. Many circRNAs have been reported to play essential roles in cancer development and have the potential to serve as a novel class of biomarkers for clinical diagnosis. However, the role of circRNA in osteosarcoma (OS) remains largely unknown. In the current study, we examined the expression level of circular RNA PVT1 (circPVT1), previously screened and identified the oncogenic ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
242
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 227 publications
(248 citation statements)
references
References 50 publications
(46 reference statements)
6
242
0
Order By: Relevance
“…For circ‐PVT1, it has been found dysregulated in some cancer cells, and a few studies emerge to display the role of circ‐PVT1 as an oncogene in various cancers . For example, circ‐PVT1 expression is elevated in gastric cancer cells compared to normal gastric epithelium cells, and is also increased in CRC cell lines compared to normal human colon epithelial cell line .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For circ‐PVT1, it has been found dysregulated in some cancer cells, and a few studies emerge to display the role of circ‐PVT1 as an oncogene in various cancers . For example, circ‐PVT1 expression is elevated in gastric cancer cells compared to normal gastric epithelium cells, and is also increased in CRC cell lines compared to normal human colon epithelial cell line .…”
Section: Discussionmentioning
confidence: 99%
“…Circular RNA PVT1 (Circ‐PVT1) has been reported to promote cell proliferation, migration and invasion but suppress cell apoptosis in several cancers, such as nonsmall cell lung cancer (NSCLC), colorectal cancer (CRC) and head/neck squamous cell carcinoma, indicating that circ‐PVT1 might function as an oncogene in these cancers . In clinical practices, the abnormally overexpressed circ‐PVT1 has shown the potential to be a predictive factor for poor prognosis in patients with different malignancies as well . Considering different cancers present with the common feature of malignant proliferation, we hypothesized that the functions of circ‐PVT1 on promoting cancer cell proliferation and suppressing apoptosis might also be existed in EOC cells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Circular RNAs (circRNAs), a category of endogenous RNAs united by a structure of closed‐loop without a 5ʹ‐3ʹ polarity, are a promising class of non‐coding RNAs capable of regulating transcriptional or posttranscriptional gene expression via functioning as microRNAs (miRNAs) sponges . Several individual circRNAs have been revealed to play essential roles in osteosarcoma pathogenesis, such as regulating cancer cell cycle, cell proliferation, and chemoresistance, and serving as prognostic biomarker in osteosarcoma patients . CircRNA La‐related RNA‐binding protein 4 (circ‐LARP4) is a novel circRNA derived from the LARP4 gene, a gene encoding La‐related RNA‐binding protein that is capable of regulating cancer cell migration and invasion .…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7] Several individual circRNAs have been revealed to play essential roles in osteosarcoma pathogenesis, such as regulating cancer cell cycle, cell proliferation, and chemoresistance, and serving as prognostic biomarker in osteosarcoma patients. [8][9][10] CircRNA La-related RNA-binding protein 4 (circ-LARP4) is a novel circRNA derived from the LARP4 gene, a gene encoding Larelated RNA-binding protein that is capable of regulating cancer cell migration and invasion. 11 Furthermore, it is reported that circ-LARP4 could inhibit cancer cell proliferation and invasion in other cancers apart from osteosarcoma.…”
Section: Introductionmentioning
confidence: 99%